Usage of the Heterologous Expression of the Antimicrobial Gene afp From Aspergillus giganteus for Increasing Fungal Resistance in Olive - Narvaez, Isabel; Khayreddine, Titouh; Pliego, Clara; Cerezo, Sergio; Jiménez-Díaz, Rafael M.; Trapero-Casas, José L.; López-Herrera, Carlos; Arjona-Girona, Isabel; Martín, Carmen; Mercado, José A.; Pliego-Alfaro, Fernando (Frontiers in Plant Science, 2018)
The antifungal protein (AFP) produced by Aspergillus giganteus, encoded by the afp gene, has been used to confer resistance against a broad range of fungal pathogens in several crops. In this research, transgenic olive plants expressing the afp gene under the control of the constitutive promoter CaMV35S were generated and their disease response against two root infecting fungal pathogens, Verticillium dahliae and Rosellinia necatrix, was evaluated. Embryogenic cultures derived from a mature zygotic embryo of cv. ‘Picual’ were used for A. tumefaciens transformation. Five independent transgenic lines were obtained, showing a variable level of afp expression in leaves and roots. None of these transgenic lines showed enhanced resistance to Verticillium wilt. However, some of the lines displayed a degree of incomplete resistance to white root rot caused by R. necatrix compared with disease reaction of non-transformed plants or transgenic plants expressing only the GUS gene. The level of resistance to this pathogen correlated with that of the afp expression in root and leaves. Our results indicate that the afp gene can be useful for enhanced partial resistance to R. necatrix in olive, but this gene does not protect against V. dahliae.